Digital Literacy Profile of Indonesian Educational Technology Students in the Era of Digital Transformation - Murti Kusuma Wirasti; Ramadhan Hamam Irawan; Mulyadi (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The development of digital technology has led to fundamental changes in the industrial world, known as the industrial transformation of the digital era. One of the serious challenges in education regarding digital technology resources is the ability to control them through algorithmic systems. This research aims to analyze and map the profile of Educational Technology students, particularly Generation Z, who are now in an increasingly mediated and digitalized learning environment. The research employs a quantitative approach with a descriptive research design. The sampling method used is total sampling, where the entire population is selected as the research sample. Data collection is conducted using a questionnaire as the instrument. The data analysis techniques include both qualitative and quantitative descriptive analysis. The research findings reveal three categories of digital literacy competencies among Indonesian Educational Technology students: communicative power, selective power, and digital-based creation. Communicative power relates to elements such as social networking, transliteracy, identity management, and self-broadcasting. The digital literacy competency related to communicative skills is categorized as very good, as is the ability to select various digital content when accessing internet-based media. However, the digital literacy competency related to creative power is in the good category, tending towards quite good.